Teacher Bullying and Mathematics Attainment: The Mediating Roles of Psycho-Socio-Emotional Factors in South-East Nigeria (Path Analysis) - Okoiye , Emmanuel Ojaga (Universal Education Jurnal Teaching and Learning, 2026)
This study investigated teacher bullying and mathematics attainment: The mediating roles of psycho-socio-emotional factors in South-East, Nigeria. The study adopted the ex-post facto research design with a sample of 2,150 Senior Secondary School Students who reported teacher bullying, had low math scores, and received counselling from their school counsellors based on their experience of bullying. Ten valid instruments have been used. Two research questions were answered at the 0.05 level of significance. Data were analysed using multiple regression (backward solution) and path analysis. The result revealed in order of magnitude shows that emotional intelligence had the highest mediating effect (16.48%) on mathematics attainment of secondary school students bullied by teachers. This is followed by self-esteem (15.65%); readiness to learn (15.22%); self-efficacy (14.83%); interest in schooling (14.83%); teacher-student consultation (13.57%) on mathematics attainment of secondary school students bullied by teachers. Also, the entire psycho-socio-emotional mediating factors were shown to contribute differentially to the mathematics attainment of secondary school students bullied by teachers. Specifically, emotional intelligence mediated most significantly to the explained variation on mathematics attainment (β = 0.23, p < .001). This is followed in magnitude of beta weights by mathematics anxiety (β = 0.18, p < .01); self-efficacy (β = 0.16, p < .05); teacher-student consultation (β = 0.08, p < .05); Interest in school (β = 0.08, p < .05); Readiness to learn (β = 0.06, p < .05). However, the mediating effect of self-esteem (β = -0.04, p < .05), dejection (β = -0.02, p < .05) and achievement motivation (β = -0.02, p < .05) were not significant on mathematics attainment of students bullied by their teachers. Therefore, it was recommended that mathematics teachers in secondary schools should endeavour to use appropriate teaching methods and communication skills that would address the learning and developmental needs of students.